A case report of mesenteric panniculitis. Issue 7 (July 2019) - Zhao, Ming-en; Zhang, Ling-qiang; Ren, Li; Li, Zhen-wei; Xu, Xiao-lei; Wang, Hai-jiu; Wang, Zhi-xin; Li, Hai-long; Bao, Yuan-yuan; Fan, Hai-ning; Yangdan, Cai-rang
A 65-year-old man had intermittent abdominal pain for the previous 2 years. This pain suddenly became worse with a fever and elevated inflammatory markers. We took a while to diagnose the patient with mesenteric panniculitis (MP). Although imaging findings suggested MP, we needed to rule out other diseases. Choosing a treatment for the patient also took some time and we finally used glucocorticoid to cure the patient.